Development of the system for gene therapy of AIDS on the basis of antisense RNAs - Shved, A.D.; Kukharenko, O.P. (Вiopolymers and Cell, 2013)
Based on adeno-associated virus derived plasmid construct that are able to synthesize in cells antisense RNAs directed against key genes of HIV. Gematopoietic human cells carrying the created structure, acquired resistance to HIV infection, as evidenced by the reduction in infectious titer of HIV in cell culture. The resulting system of intracellular resistance to retrovirus can be seen as a model of gene therapy of AIDS. На базі аденоасоційованого вірусу отримано плазмідну конструкцію, здатну до синтезу в клітині антисенсових РНК, спрямованих проти ключових генів ВІЛ. Гемопоетичні клітині людини, що несуть в собі створену конструкцію, набувають стійкості до ВІЛ-інфекції, що засвідчує зниження інфекційного титру ВІЛ у культурі клітин. Одержану систему внутрішньоклітинної резистентності до ретровірусу можна розглядати як модель генотерапії СНІДу. На базе аденоассоциированного вируса получена плазмидная конструкция, способная синтезировать в клетке антисмысловые РНК, направленные против ключевых генов ВИЧ. Гемопоетические клетки человека, несущие созданную конструкцию, приобретают устойчивость к ВИЧ-инфекции, о чем свидетельствует снижение инфекционного титра ВИЧ в культуре клеток. Полученную систему внутриклеточной резистентности к ретровирусу можна рассматривать как модель генотерапии СПИДа.